Aggressive behavior of preschool children in selected progressive preschools in Quezon City a developmental perspective - Sievert, Angelita Rosario O. (2001)
Many studies have been done on the aggressive behavior of young children, yet, only a number focus on the development of aggression. This study aimed to know more about the developmental perspective of aggression. Specifically, it hoped to gain information on the aggressive acts manifested by children at ages three and five, as well as the events that instigate these behaviors. It also intended to know the differences in these variables between gender. Sixty children randomly chosen from three progressive preschools in Quezon City were the subjects. They were observed during their freeplay and outdoor play periods for 15 minutes each for five days. Results from the two way analysis of variance done on the study showed that three year olds, rather than fives, were more physically aggressive while five year olds were more verbally aggressive. It further showed that males were significantly more physically aggressive than the females. No significant difference was seen in verbal aggression in terms gender. Events that trigger aggressive behavior vary as age increases only on verbal derogation, where five year olds were more prone to, and not on the another classifications. The instigating events vary significantly between gender on bodily contact, as well as by those that were triggered by these events more frequently than the females.